THE SOVEREIGNTY AND RETENTION OF THE HOMO SACER SUBJECTS IN THE ROOSTER BAR NOVEL - Anshoor, Hafiz Naufal (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
The primary narration of The Rooster Bar novel is about the trapped life of the three characters in a scholarship program for poor people. In the story, the D.C. offered the United States of America scholarship program. The scholarship requires the characters to pay all the loans after they graduate. Thus, these characters could only have one specific scholarship program for poor people. This study analyzed the strategy of sovereignty in retaining the homo sacer subjects and the forms of resistance from three characters to escape from the retention as the homo sacer group. The research methodology is descriptive and qualitative by taking note of the essential data related to the formal objects and analyzing them. The novel showed that the minor and poor community, especially students, were allocated into one zone which in a high educational institution to fulfill the scholarship scheme as the realization of homo sacer retention. This situation reduces the poor student from the rights and protection in the legal order. The retention is based on a state of exception, sovereignty, and apparatus as the unity to keep the characters failed to flee from the homo sacer status.